HUBUNGAN PERSONAL HYGIENE DENGAN KEJADIAN SKABIES PADA WARGA BINAAN RUTAN KELAS IIB PRAYA TAHUN 2021 - Dewantoro, Wisnu; Sofyandi, Arif; Marzuki, Ismail (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2023)
Scabies is infectious skin disease which is caused by mite Sarcoptes scabei varieta hominis female. Based on the result of interview at IIB Jail in Praya, people with scabies in 2020 was in the amount of 60 people every month and in 2021 was in the amount of 65 people up to November 2021. This study aimed to analyze personal hygiene and scabies on inmates at III B Class Jail in Praya 2021. This study used analytic observation by case control design. Number of samples was in the amount of 100 samples divided into 50 case samples ant other 50 control samples. Data were analyzed by univariate and bivariate analyses by chi square test. Based on data analysis, it was found that there were 36 inmates (72%) have bad personal hygiene and got scabies. There were 46 inmates (92%) have good personal hygiene and did not get scabies. The OR value in this study was 29.571 meant the inmates who have bad personal hygiene got risk more than 29 times to get scabies compared with those inmates who have good personal hygiene. Statistic test by chi square showed p value was 0.000. It is expected to head officers of II B Class jail in Praya to prevent the spread of scabies by creating a self-isolation room for those inmates who got scabies to separate with other inmates who did not get scabies and by increase knowledge personal hygiene to inmates.